Praktek Nilai Moderasi Beragama dalam Dinamik Masyarakat Kampung Naramben Distrik Skanto Kabupaten Keerom - Musleh Apripa; Idrus Al Hamid; A. Ubaidillah (Hidayah : Cendekia Pendidikan Islam dan Hukum Syariah, 2026)
This research is motivated by the diversity of ethnicities, cultures, and religions in Indonesia, which makes religious moderation a crucial key to creating harmony and tolerance, including in Naramben Village, Skanto District, Keerom Regency. The research problem formulation focuses on how religious moderation is practiced and its impact on community dynamics in the village. The aim is to determine the practice and impact of religious moderation in the Naramben Village community. The results of the study indicate that the practice of religious moderation is realized through deliberation and the rejection of violence. As a result, strong social harmony is established, characterized by mutual cooperation and mutual respect regardless of differences. The results of this study are also in line with Peter L. Berger's social construction theory and Lukman Hakim Saifuddin's views, where social reality is shaped through interaction and concrete actions. In conclusion, religious moderation has become the main foundation of social harmony in Naramben Village. As a suggestion, this research has implications for adding to the scientific body and providing input for the village government in formulating policies related to the practice of religious moderation.